Inhibitory Effect and Mechanism of Dancong Tea from Different Harvesting Season on the α-Glucosidase Inhibition In Vivo and In Vitro - Rourou Wen; Xianghua Chai; Pingping Wang; Kegang Wu; Xuejuan Duan; Jiasi Chen; Tong Zhang; Liya Zeng (Foods)
Tea polyphenols have been reported to decrease the rate of starch hydrolysis by inhibiting α-glucosidase. However, the effect of the tea harvesting season and the structure of catechin monomers on the inhibitory activity of α-glucosidase is not understood. In this study, the inhibitory effect and underlying mechanism of four seasons of Dancong tea against α-glucosidase were investigated by in vivo and in vitro experiments, multi-spectroscope and molecular dynamic. The Dancong tea harvested in spring and winter showed a stronger inhibitory effect on α-glucosidase due to a higher content of catechin, especially EGCG ((-)-epigallocatechin-3-gallate). The results of in vivo and in vitro experiments showed that EGCG and ECG ((-)-epicatechin-3-gallate) with a higher content of gallate and hydroxyl groups exhibited a stronger inhibitory effect on starch hydrolysis, rise of postprandial blood glucose and activities of α-glucosidase compared to EGC ((-)-epigallocatechin) and EC ((-)-epicatechin). These gallate and hydroxy groups were more effective in interacting with the amino acid residues in the active site of α-glucosidase, leading to structural changes in the enzyme. Certainly, the inhibitory effect of Dancong tea on α-glucosidase explains one of the mechanisms by which it helps alleviate diabetes; the other hypoglycaemic mechanisms of Dancong tea will be further explored.